Penerapan Pendekatan Healing Environment Terhadap Perencanaan dan Perancangan Healing Centre for Urban Stress di Denpasar: Bahasa Indonesia - I Putu Eka Dana Prastiya Narayana Putra; I Gede Surya Darmawan; Ida Bagus Gede Parama Putra; Kadek Tania Utami Putri (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
The Healing Center is a healing center for people affected by mental health disorders which involve psychological effects. Currently in Indonesia, especially in Bali, mental health is one of the problems that must be addressed, it's just that our society still often remembers the importance of mental health. It has been proven that the number of people suffering from mental health disorders in Indonesia, especially in Bali, is quite high. This is the urgency of providing Healing Center Facilities as a healing medium for people with mental health disorders. Providing an educational area in the Healing Center Design is also very important, explaining how to empower individuals or local communities to be able to maintain their mental health in facing situations. anything, especially in life. There is great hope that the provision of this Healing Center Facility will be able to reduce the number of people suffering from mental health disorders and make this facility an education for the wider community about the importance of maintaining mental health.